Planificación en la Facultad: 15 años abriendo camino - Valencia-Giraldo, Asdrúbal; Arteaga-Rueda, Jhon Jairo; Mejía-Cortés, Jorge Hernán; Mejía-Ruiz, Roberto; Ruiz-Córdoba, Jairo; Restrepo-González, Guillermo; Duitama-Muñoz, Freddy; Zuluaga-Castaño, Ana Cristina (Revista Facultad de Ingeniería Universidad de Antioquia, 1998)
(Sin resumen)